Peran Filsafat Dalam Perkembangan Konsep Bilangan Matematika - Febriana, Rina; Khairiani, Dian (Sepren, 2024)
Philosophy and mathematics are very closely related and cannot be separated. Philosophy can open up views on how philosophy has shaped the understanding and application of number concepts. The contribution of ancient and modern philosophers in shaping our thinking about numbers, as well as expanding our view of numbers beyond just the concept of numbers. From Pythagoras's view of numbers as the basis of the structure of the universe to Bertrand Russell's contributions to mathematical logic, this article highlights how philosophy has helped expand our understanding of numbers. Discusses an in-depth understanding of various types of numbers, such as natural numbers, integers, and irrational numbers, as well as the mathematical properties that underlie number operations. The research method used is the library method by collecting data from various sources to provide rich insight into the relationship between philosophy and mathematics in the context of the concept of number. The results confirm the importance of the contribution of philosophy in defining, enriching, and developing the concept of number in mathematics